PENGATURAN TINDAK PIDANA PERSETUBUHAN TERHADAP HEWAN DALAM HUKUM PIDANA INDONESIA - Abdurrahman, Abdurrahman; Firdaus, Emilda; Erdiansyah, Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Bestiality, which can also be called zoophilia, is the involvement of contact and sexual activitybetween humans and animals. Of course it is clear that this action is not in accordance with the norms in thecommunity. The case of Sutarya's grandfather in Bali, the case of a young man with a GA in Bali, the case ofa young man with the initials AS in Tasikmalaya, and the case of Hendro in Bone Sulawesi as evidence thatthis heinous act occurred. Not regulating bestiality in Indonesian law, makes it unclear about lawenforcement officials in enforcing the law. So that the sanctions given to the perpetrators who were foundproven, in Bali, were given traditional sanctions and carried out traditional ceremonies to clean the souls ofthe perpetrators, the village, and also the animals that became objects. This act does not only violate theprevailing norms in the community, but also economic losses experienced by animal owners. including acase of bestiality in Tasikmalaya which resulted in 300 chickens dead. Cows belonging to a resident in Baliwho were the object of Sutarya's grandfather also had to be drowned in accordance with the localtraditional ceremony. Legal certainty is needed to determine more appropriate regulations to be applieduniformly.The purpose of this study is to determine the arrangement of criminal acts of sexual intercourse withanimals in Indonesia. Especially criminal law as ultimum remedium. And to find out the impending criminallaw policy regarding sexual intercourse with animals in Indonesia. There are five principles of animalwelfare based on legislation and need to be considered by humans as animal owners: free from hunger,thirst, pain, discomfort, fear, feeling depressed, pain, injury, illness, and free to express patterns of behaviornormal. In addition, animals must be protected from physical and psychological abuse.Arrangement of criminal acts of intercourse with animals in Indonesia has not been regulated inwriting in the laws and regulations. In the Indonesian Penal Code the law is not regulated concretely.Especially in Article 302 relating to animal abuse. in Article 66 of Law Number 18 of 2009 concerningAnimal Husbandry and Animal Health which protects animals from abuse and abuse is not accompanied bycriminal sanctions. As well as in the amendment law also does not mention the prohibition of criminal actsof intercourse with animals. Government Regulation Number 95 of 2012 concerning the Health ofVeterinary Communities and Animal Welfare also does not regulate bestiality. As well as criminal lawpolicy that is carried out by the method of evolutionary approach that is by amending and inserting newrules in an article relating to violence against animals. letter c Article 501 of RUU KUHP.Keywords: Arrangements, - Bestiality, - Animals, - Criminal Law Policies.